A Systematic Study on Vitex Tourn. (Verbenaceae) in Sabah And Sarawak, Malaysia - Phongoudome, Chanhsamone (2000)
This thesis comprised a systematic study of the genus Vitex Tourn. (Verbenaceae) in Sabah and Sarawak, Borneo. The study was mainly based on 1,064 herbarium specimens obtained from seven herbaria. Additional information on the species was also gathered from some field observations of natural populations, with the incorporation of new characters such as inflorescence architecture and its degree of hairiness, epidermal structures of leaves through the scanning electron microscopy. The genus Vitex comprises 12 species i.e. V. trifolia, V. ovata, V. neg undo, V. cannabifolia, V. pinnata, V. quinata, V. parviflora, V. gamosepa/a, V. vestita, V. secundiflora, V, longipes and V. f1ava; the latter three species are endemic to Borneo. Taxonomic evidences were obtained based on the morphology, anatomy, palynology, ecology and distribution of the taxa, which were finally subjected to numerical methods. The vegetative morphological characters found to be diagnostic where growth form, habit and buttress formation; leaf characteristics such as arrangement, shape, apex, base, margin, number of secondary nerves, petiole and petiolule length, texture, the adaxial and abaxial surface, size length and width; reproductive characters includes inflorescence characteristics such as position, architecture, length and width; flower characteristics such as perianth and colour of petals, and of calyx, fruiting calyx; and, fruit features such as size and seeds.